Electrode assembly including separator having conductive layer formed thereon and battery cell including the same
The three-dimensional electrode assembly with a conductive layer and inorganic structure addresses the cracking issues in silicon-based lithium batteries, ensuring stable conductive networks and enhanced energy density.
Patent Information
- Application Number
- JP2022579103
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-11
- Filing Date
- 2021-08-18
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2041-08-18
AI Technical Summary
Existing lithium secondary batteries using silicon as a negative electrode active material face issues with cracking and conductive network disruption due to the large expansion and contraction during charge and discharge cycles, leading to increased resistance and reduced battery performance.
A three-dimensional electrode assembly is developed with a separation film containing a conductive layer that covers the silicon active material, where the conductive layer is thicker than 50% of the D50 particle diameter of the silicon, and includes inorganic layers with controlled gaps to prevent cracking and maintain the conductive network.
The solution effectively prevents the conductive network from being disrupted, maintains electronic conductivity, and enhances energy density by allowing the use of high-capacity silicon while minimizing the negative electrode thickness, thus improving battery performance and cycle life.
Smart Images

Figure 0007625321000001
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 2020-0116731 filed on September 11, 2020, and all contents disclosed in the documents of the Korean patent application are incorporated herein by reference.
[0002] The present invention relates to an electrode assembly including a separator having a conductive layer formed thereon, and a battery cell including the electrode assembly, and more particularly, to an electrode assembly including a separator having a conductive layer formed thereon to prevent a conductive network from being short-circuited due to damage to a negative electrode mixture layer caused by expansion and contraction caused by charging and discharging a secondary battery, and a battery cell including the electrode assembly. [Background technology]
[0003] The lithium secondary battery may be manufactured by incorporating an electrode assembly including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode into a metal can or a laminate sheet case, and injecting an electrolyte therein.
[0004] Research into increasing the energy capacity per unit volume of lithium secondary batteries is still ongoing. When graphite is used as the negative electrode active material, a method of thickening the negative electrode mixture layer is used. In this case, problems such as cracking of the negative electrode mixture layer, swelling during coating, and detachment of the negative electrode mixture layer from the current collector occur.
[0005] If part of the negative electrode active material is replaced with a high-capacity silicon (Si) material, the electrode mixture layer can be formed thin, solving the above problems.
[0006] Silicon expands and contracts more during charging and discharging than other materials, which causes many surface cracks and shorts the conductive network in the negative electrode mixture layer, which increases the resistance of the battery cell.
[0007] Patent Document 1 relates to a highly safe non-aqueous electrolyte secondary battery that can prevent short circuits and explosions even when it is overcharged due to the application of a high voltage, and discloses a separator having a conductive layer formed thereon, the resistivity of which falls within a certain range.
[0008] Patent Document 1 recognizes the effect of preventing overcharging, but does not recognize how to solve the problem of dendrite formation in a negative electrode using a silicon active material, and the problem of excessive expansion and contraction of the silicon active material.
[0009] Patent Document 2 relates to a lithium secondary battery using a battery separator coated with a conductive layer, and is a technology for preventing highly reactive dendritic lithium metal from being cut and separated from the negative electrode when a lithium metal negative electrode is used.
[0010] US Pat. No. 5,399,633 does not recognize the problems associated with using silicon anodes and does not provide any solutions to these problems.
[0011] When using a silicon negative electrode that expands and contracts greatly, an effective solution has not yet been presented to prevent the performance of a battery cell from deteriorating due to the occurrence of cracks in the negative electrode mixture layer. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Korean Patent Publication No. 2012-0062713 [Patent Document 2] Korean Patent Publication No. 1999-010035 Summary of the Invention [Problem to be solved by the invention]
[0013] The present invention has been made to solve the above problems, and has an object to provide an electrode assembly including a separator having a conductive layer formed on its surface to cover a silicon active material protruding from a surface of a negative electrode mixture layer in order to prevent a conductive network from being destroyed due to excessive expansion and contraction of a negative electrode containing a silicon active material, and a battery cell including the same. [Means for solving the problem]
[0014] To achieve the above object, the electrode assembly according to the present invention includes a positive electrode having a positive electrode mixture layer formed on at least one surface of a positive electrode current collector, a negative electrode having a negative electrode mixture layer formed on at least one surface of a negative electrode current collector, and a separator interposed between the positive electrode and the negative electrode, the negative electrode mixture layer includes a silicon active material, and a conductive layer is formed on at least one surface of the separator, and a thickness of the conductive layer may be greater than 50% of a D50 particle size of the silicon active material.
[0015] In the electrode assembly according to the present invention, the separator may include a separator substrate made of a porous substrate, an inorganic layer formed on at least one surface of the separator substrate, and a conductive layer formed on an outer surface of the inorganic layer.
[0016] In the electrode assembly according to the present invention, a first inorganic layer is formed on one side of the separator substrate, and a second inorganic layer is formed on the other side of the separator substrate, and a conductive layer may be formed only on one of the first and second inorganic layers that faces the negative electrode.
[0017] In the electrode assembly according to the present invention, the conductive layer may include a conductive material and a binder.
[0018] In the electrode assembly according to the present invention, the conductive layer may have a thickness that is 80% to 120% of the D50 grain size of the silicon active material.
[0019] In the electrode assembly according to the present invention, the negative electrode active material included in the negative electrode mixture layer may be composed of 100% silicon active material.
[0020] In the electrode assembly according to the present invention, the inorganic layer may have a structure in which voids are formed therein.
[0021] In the electrode assembly according to the present invention, the size of the voids formed in the inorganic layer may be smaller than the size of the voids formed in the separator substrate.
[0022] In the electrode assembly according to the present invention, the conductive layer may have a porous structure.
[0023] In the electrode assembly according to the present invention, the loading amount of the positive electrode may be 4 to 10 times the loading amount of the negative electrode.
[0024] The present invention also provides a battery cell in which the electrode assembly is housed in a battery case made of a metal can or a laminate sheet.
[0025] The present invention provides a battery pack including the battery cell as a unit cell.
[0026] Furthermore, the present invention can be provided in various configurations in which the above-mentioned inventions can be combined. Effect of the Invention
[0027] As described above, in the electrode assembly according to the present invention, the conductive layer formed on the surface of the separator can function as a conductive network of the negative electrode mixture layer, so that even when cracks occur in the negative electrode mixture layer due to excessive expansion and contraction of the negative electrode active material, the electron transfer path can be prevented from being interrupted.
[0028] Furthermore, by limiting the thickness of the conductive layer to a certain range, it is possible to prevent the ion conductivity and output characteristics from being reduced due to the addition of the conductive layer.
[0029] In addition, since a high-capacity silicon active material is used, the negative electrode mixture layer can be formed thinner at the same capacity ratio than when a carbon negative electrode active material is used, and the energy density can be improved by reducing the thickness of the battery cell. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] Hereinafter, the present invention will be described in detail with reference to the preferred embodiments that will enable those skilled in the art to easily carry out the present invention. However, in describing the principles of operation of the preferred embodiments of the present invention in detail, if it is determined that the detailed description of related known functions or configurations may unnecessarily obscure the gist of the present invention, the detailed description thereof will be omitted.
[0031] In addition, throughout the specification, when one part is said to be connected to another part, this includes not only a direct connection but also an indirect connection through another element in between. Furthermore, the inclusion of one component does not mean the exclusion of other components, but may further include other components, unless otherwise specified to the contrary.
[0032] Moreover, the limitations set forth in the dependent claims may apply to all embodiments described herein.
[0033] Moreover, throughout the description of the present invention and the claims, the singular includes the plural, unless specifically stated otherwise.
[0034] Furthermore, throughout the description of the invention and claims of this application, unless otherwise stated, "or" includes "and." Therefore, "including A or B" means all three cases including including A, including B, or including both A and B.
[0035] Additionally, all numerical ranges include the endpoints and all intermediate values therebetween unless expressly stated to exclude.
[0036] The electrode assembly according to the present invention includes a positive electrode having a positive electrode mixture layer formed on at least one surface of a positive electrode current collector, a negative electrode having a negative electrode mixture layer formed on at least one surface of a negative electrode current collector, and a separator interposed between the positive electrode and the negative electrode, the negative electrode mixture layer including a silicon active material, and a conductive layer formed on at least one surface of the separator, and a thickness of the conductive layer may be greater than 50% of a D50 particle size of the silicon active material.
[0037] The electrode assembly may be a stack-type electrode assembly in which one or more positive electrodes and one or more negative electrodes are stacked with a separator interposed therebetween; a stack-folding type electrode assembly in which each stack-type unit cell including a positive electrode and a negative electrode is wound up with a separator sheet; a lamination-stack type electrode assembly in which each stack-type unit cell including a positive electrode and a negative electrode is stacked with a separator interposed therebetween; or a winding type electrode assembly in which one positive electrode and one negative electrode are wound up with a separator interposed therebetween.
[0038] The positive electrode is prepared, for example, by applying a positive electrode mixture containing a positive electrode active material onto a positive electrode current collector and then drying the applied positive electrode mixture. If necessary, the positive electrode mixture may selectively further include a binder, a conductive material, a filler, and the like.
[0039] The positive electrode current collector is generally made to a thickness of 3 μm to 500 μm. Such a positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and the positive electrode current collector may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may have fine irregularities on its surface to increase the adhesive force of the positive electrode active material, and may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0040] The positive electrode active material is a material capable of undergoing an electrochemical reaction and contains two or more transition metals as a lithium transition metal oxide. Examples of the positive electrode active material include layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) substituted with one or more transition metals; lithium manganese oxide substituted with one or more transition metals; and lithium manganese oxides having the chemical formula LiNi 1-y M y Lithium nickel oxide represented by the formula: LiO2 (wherein M=Co, Mn, Al, Cu, Fe, Mg, B, Cr, Zn, or Ga, and contains one or more of the above elements, and 0.01≦y≦0.8); 1+z Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O2, Li 1+z Ni 0.4 Mn 0.4 Co 0.2 Li like O2 etc. 1+z Ni b Mn c Co 1-(b+c+d) M d O (2-e) A e (wherein, -0.5≦z≦0.5, 0.1≦b≦0.8, 0.1≦c≦0.8, 0≦d≦0.2, 0≦e≦0.2, b+c+d<1. M=Al, Mg, Cr, Ti, Si or Y, and A=F, P or Cl.) Lithium nickel cobalt manganese composite oxide represented by the formula Li 1+x M 1-y M' y PO 4-z X z (wherein M=transition metal, preferably Fe, Mn, Co, or Ni; M′=Al, Mg, or Ti; X=F, S, or N; −0.5≦x≦0.5, 0≦y≦0.5, and 0≦z≦0.1), but the present invention is not limited to these.
[0041] The conductive material is usually added in an amount of 1% by weight to 30% by weight based on the total weight of the mixture including the positive electrode active material. The conductive material is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and examples of the conductive material include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0042] The binder is a component that helps bind the active material and the conductive material and the current collector, and is usually added in an amount of 1 to 30% by weight based on the total weight of the mixture including the positive electrode active material. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer, styrene-butylene rubber, fluororubber, and various copolymers.
[0043] The filler is selectively used as a component that suppresses the expansion of the electrode, does not induce chemical changes in the battery, and is not particularly limited as long as it is a fibrous material. Examples of the filler that can be used include olefin polymers such as polyethylene and polypropylene; glass fibers, carbon fibers, and other fibrous materials.
[0044] The negative electrode is manufactured, for example, by applying a negative electrode mixture containing a negative electrode active material onto a negative electrode current collector and then drying the applied mixture. The negative electrode mixture may contain various components such as the conductive material, binder, and filler as described above, as necessary.
[0045] The negative electrode current collector is generally made to have a thickness of 3 μm to 500 μm. Such a negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity. Examples of the negative electrode current collector include copper, stainless steel, aluminum, nickel, titanium, fired carbon, those obtained by surface-treating the surface of copper or stainless steel with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, and the like. Further, similar to the positive electrode current collector, the negative electrode current collector can also strengthen the binding force of the negative electrode active material by forming fine irregularities on the surface, and can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, non-woven fabric bodies, and the like.
[0046] Examples of the negative electrode active material include silicon; carbon such as graphitizable carbon and graphite-based carbon; Li x Fe2O3(0≦x≦1), Li x WO2(0≦x≦1), Sn x Me 1-x Me’ y O z (Me = Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) and other metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials, etc. can be used. Specifically, silicon (Si) can be used.
[0047] Furthermore, in addition to the silicon active material, other silicon-containing substances may be included to the extent that they do not affect the effects intended in the present invention. For example, SiO, SiO2 or a mixture thereof; Sn-based substances such as Sn, SnO and SnO2; carbon-based substances such as artificial graphite, natural graphite, amorphous hard carbon and low-crystalline soft carbon; metal composite oxides such as lithium titanate oxide; or a mixture of two or more of these can be included.
[0048] Specifically, the silicon active material is a component that combines with lithium ions that migrate from the positive electrode during a charging reaction to cause an electrochemical reaction, and has an excellent theoretical capacity of 4,200 mAh / g. Therefore, the higher the content of the silicon active material contained in the negative electrode mixture, the higher the capacity of the battery cell that can be manufactured. The negative electrode active material contained in the negative electrode mixture may be 80% or more of silicon active material, more specifically, 90% or more, and more specifically, may be composed of 100% silicon active material.
[0049] Meanwhile, in order to prevent the occurrence of non-uniformity between the positive and negative electrodes during the manufacture of the electrode assembly and the occurrence of unnecessary waste of the positive or negative electrodes, it is necessary to take into consideration that the silicon active material has a high capacity. In particular, the loading amount of the positive electrode may be formed in a range of 4 to 10 times, and more particularly, in a range of 4 to 6 times, based on the loading amount of the negative electrode.
[0050] The D50 particle size of the silicon particles may be in the range of 0.1 μm to 20 μm, 0.2 μm to 15 μm, 0.8 μm to 10 μm, 1 μm to 8 μm, or 2 μm to 7 μm. Silicon particles having a D50 particle size in the above numerical range are advantageous in terms of conductive network formation when using the same content of conductive material, compared with silicon particles having a larger or smaller average particle size.
[0051] In this specification, the term "D50 particle size" refers to the representative diameter of two or more types of particles with different particle sizes, and is the particle size that corresponds to 50% of the weight percentage in a particle size distribution curve. In other words, the D50 particle size refers to the diameter of particles that pass 50% of the cumulative weight in a particle size distribution curve, and is understood to have the same meaning as the diameter of particles that pass through a sieve of the size that passes 50% of the total.
[0052] The average particle size of the silicon particles can generally be measured using X-ray diffraction (XRD) analysis or an electron microscope (SEM, TEM), or the like.
[0053] The binder, conductive material, and other components added as necessary are the same as those described for the positive electrode.
[0054] In addition, other components such as viscosity modifiers, adhesion promoters, etc. may be further included either selectively or in combination of two or more.
[0055] The viscosity modifier is a component that adjusts the viscosity of the electrode mixture so that the electrode mixture can be mixed and applied to the current collector easily, and may be added in an amount of up to 30 wt % based on the total weight of the negative electrode mixture. Examples of such viscosity modifiers include, but are not limited to, carboxymethyl cellulose, polyvinylidene fluoride, etc.
[0056] The adhesion promoter is an auxiliary component added to improve the adhesion of the active material to the current collector, and may be added in an amount of 10 wt % or less compared to the binder. Examples of the adhesion promoter include oxalic acid, adipic acid, formic acid, acrylic acid derivatives, and itaconic acid derivatives.
[0057] The separation membrane includes a separation membrane substrate made of a porous substrate, an inorganic layer formed on at least one surface of the separation membrane substrate, and a conductive layer formed on an outer surface of the inorganic layer.
[0058] As the separation membrane substrate, an insulating thin film having high ion permeability and mechanical strength is used. The pore diameter of the separation membrane is generally 0.01 μm to 10 μm, and the thickness is generally 5 μm to 300 μm. As such a separation membrane, for example, a chemically resistant and hydrophobic olefin polymer such as polyethylene or polypropylene; a sheet or nonwoven fabric made of glass fiber or polyethylene, etc. is used. When a solid electrolyte such as a polymer is used as the electrolyte, the solid electrolyte can also serve as the separation membrane.
[0059] The inorganic layer is formed by coating the mixture of inorganic particles and a binder polymer on the separator substrate, and the porous inorganic layer is formed on the porous separator substrate. The separator including such an inorganic layer has an advantage of being more heat resistant than a conventional separator substrate having only a separator substrate.
[0060] In general, in a lithium secondary battery, dendrites may be formed by plating lithium ions that have moved from a positive electrode to a negative electrode on the surface of the negative electrode. When the positive electrode and the negative electrode are connected due to the growth of the dendrites, self-discharge or low voltage occurs due to the flow of current. However, when a porous structure with irregular voids is included inside, such as the separator substrate and the inorganic layer, the growth of dendrites can be suppressed.
[0061] In addition, when the voids formed in the inorganic layer are smaller than the voids formed in the separation membrane substrate, i.e., when the void structure is made smaller and more complex in the inorganic layer than in the separation membrane substrate, the effect of inhibiting the dendrites from growing toward the positive electrode can be further improved.
[0062] The inorganic material constituting the inorganic layer is not particularly limited as long as it is generally used in manufacturing an inorganic layer of a separator for a secondary battery, and may be at least one selected from the group consisting of (a) inorganic materials having piezoelectricity, and (b) inorganic materials having lithium ion transport ability.
[0063] The inorganic material having piezoelectricity is a material that is non-conductor under normal pressure, but when a certain pressure is applied, it has a physical property of conducting electricity due to a change in its internal structure. It not only exhibits high dielectric constant characteristics with a dielectric constant of 100 or more, but also has the function of generating charges when stretched or compressed by applying a certain pressure, so that one side becomes positively charged and the other side becomes negatively charged, generating a potential difference between both sides.
[0064] When an inorganic material having the above characteristics is used as a porous active layer component, if an internal short circuit occurs between the positive and negative electrodes due to an external impact such as a needle-shaped conductor, the inorganic material layer coated on the separator prevents the positive and negative electrodes from coming into direct contact with each other, and a potential difference occurs within the particles due to the piezoelectricity of the inorganic material, thereby allowing electrons to move between the positive and negative electrodes, i.e., a minute current to flow, resulting in a gradual decrease in the battery voltage and improved safety.
[0065] Examples of inorganic substances having piezoelectricity include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT), Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiC, and mixtures thereof, but are not limited thereto.
[0066] The inorganic material having lithium ion transport ability refers to an inorganic material that contains lithium element and has a function of transporting lithium ions without storing lithium. The inorganic material having lithium ion transport ability can transport and transport lithium ions through a type of defect present inside a particle structure, thereby improving the lithium ion conductivity in a battery and thereby improving the battery performance.
[0067] Examples of inorganic substances having the lithium ion transfer ability include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 <x<2、0<y<3)、リチウムアルミニウムチタンホスフェート(Li x Al y Ti z(PO4)3, where 0 < x < 2, 0 < y < 1, 0 < z < 3, such as 14Li2O - 9Al2O3 - 38TiO2 - 39P2O5, (LiAlTiP) x O y series glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, where 0 < x < 2, 0 < y < 3), Li 3.25 Ge 0.25 P 0.75 such as lithium germanium thiophosphate (Li x Ge y P z S w , where 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride such as Li3N (Li x N y , where 0 < x < 4, 0 < y < 2), SiS2 - based glass such as Li3PO4 - Li2S - SiS2 (Li x Si y S z , where 0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5 - based glass such as LiI - Li2S - P2S5 (Li x P y S z , where 0 < x < 3, 0 < y < 3, 0 < z < 7) and one or more selected from the group consisting of these mixtures, but not limited thereto.
[0068] Further, the inorganic substance may be a metal hydroxide or a hydroxide of a metal oxide represented by the following formula.
[0069] M(OH) x (In the above formula, M is B, Al, Mg, Co, Cu, Fe, Ni, Ti, Au, Hg, Zn, Sn, Zr or an oxide thereof, and x is an integer from 1 to 4.)
[0070] The binder constituting the inorganic layer is not particularly limited as long as it is generally used in the manufacture of an inorganic layer of a separator for a secondary battery. Examples of the binder include any one binder polymer selected from the group consisting of polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, and carboxymethyl cellulose, or a mixture of two or more of these.
[0071] The solvent for forming the inorganic layer may be N-Methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), tetrahydrofuran (THF), methylethylketone (MEK), dimethylacetamide (DMAC), or dimethylsulfoxide (DMSO).
[0072] Since the electrode assembly according to the present invention includes a silicon active material as the negative electrode active material, which is subject to a large volume change due to charging and discharging, the negative electrode mixture layer is likely to crack or break, resulting in separation from the negative electrode current collector. As a result of the reduced morphological stability of the negative electrode mixture layer, a problem may occur in that the conductive network, which serves as a path for electron movement, is broken. In other words, when the negative electrode mixture layer is cracked, the conductive network may be broken, cutting off the path for electron movement, resulting in a problem of reduced battery performance.
[0073] In this way, in order to compensate for cracking of the conductive network of the negative electrode mixture layer, a conductive layer is formed on the outermost surface of the separator that is in direct contact with the negative electrode, so that even if the negative electrode mixture layer is cracked due to excessive expansion and contraction of the silicon active material, the conductive layer can compensate for the damaged conductive network function of the negative electrode mixture layer.
[0074] The conductive layer may essentially include a conductive material having electrical conductivity, and may further include a binder to maintain a bond between the conductive materials and to ensure adhesion to the inorganic layer.
[0075] The conductive material is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. Examples of the conductive material that can be used include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fiber and metal fiber; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0076] The binder is a component that does not induce chemical changes in the battery and helps to bond between conductive materials. Examples of the binder include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber, and various copolymers.
[0077] In one specific example, the thickness of the conductive layer may be formed to be 80% to 120% of the D50 grain size of the silicon active material.
[0078] The thicker the conductive layer, the more likely it is that the conductive network of the negative electrode mixture layer will be maintained. However, as the overall thickness of the separator increases, the distance between the electrodes increases, which may result in a problem of reduced ion conductivity and reduced output characteristics of the battery cell.
[0079] Meanwhile, considering that cracks mainly occur on the surface of the negative electrode mixture layer because current density is concentrated on the surface side of the negative electrode mixture layer, and that the silicon active material expands by about 130% to 150%, it is preferable that the conductive layer be added in a form that covers the silicon active material when the silicon active material expands and protrudes during full charge.
[0080] In addition, if the thickness of the conductive layer is formed smaller than the D50 particle size of the silicon active material, when the silicon active material expands to the maximum, it may expand to the inorganic layer, but the resistance of the silicon active material region that expands to the non-conductive inorganic layer increases rapidly.
[0081] Therefore, the thickness of the conductive layer can be selectively formed in the range of 80% to 120% of the D50 grain size of the silicon active material.
[0082] In one specific example, a first inorganic layer is formed on one side of the separation membrane substrate, and a second inorganic layer is formed on the other side of the separation membrane substrate, and a conductive layer may be formed only on the inorganic layer of the first inorganic layer or the second inorganic layer that faces the negative electrode.
[0083] For example, the first and second inorganic layers may be formed by dip coating, and the conductive layer may be formed by die coating or slot coating.
[0084] In this way, when a conductive layer is formed only on the inorganic layer of the separator facing the negative electrode, problems caused by cracking of the negative electrode mixture can be alleviated and an increase in the thickness of the separator can be minimized. This prevents a decrease in energy density compared to when the conductive layer is formed on each of the first inorganic layer and the second inorganic layer.
[0085] However, during repeated charging and discharging of the battery cell, the positive electrode mixture layer may expand and contract repeatedly, which may cause breakage or cracks. However, when the conductive layer is formed on each of the first inorganic layer and the second inorganic layer, even if the conductive network of the positive electrode and the negative electrode is destroyed, this can be compensated for.
[0086] In one specific example, the conductive layer may be made of a porous structure.
[0087] Since the anode of the present invention includes a silicon active material that has a large volume change, the conductive layer is provided to prevent the expanded silicon active material from expanding into the inorganic layer of the separator. In addition, if the conductive layer has a porous structure, when the silicon active material expands, the conductive layer contracts to buffer the increase in volume caused by the expansion of the silicon active material, thereby mitigating an increase in the overall thickness of the electrode assembly caused by the expanded silicon active material.
[0088] Therefore, it is possible to reduce the degree of thickness change of the electrode assembly caused by charging and discharging the battery cell.
[0089] In addition, since the conductive layer has a porous structure, it is possible to prevent the ionic conductivity of lithium ions from decreasing.
[0090] The present invention also includes a battery cell in which the electrode assembly is housed in a rectangular or cylindrical metal can, and a battery cell in which the electrode assembly is housed in a pouch-type battery case made of a laminate sheet.
[0091] The present invention also includes a battery pack including the battery cell as a unit cell, and a device including the battery pack.
[0092] Of course, the device may be, for example, a laptop, a netbook, a tablet PC, a mobile phone, an MP3, a wearable electronic device, a power tool, an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), an electric bicycle (E-bike), an electric scooter, an electric golf cart, or a power storage system, but is not limited to these.
[0093] Such battery packs and devices are well known in the art and will not be described in detail herein.
[0094] Hereinafter, the present invention will be described with reference to examples, which are for easier understanding of the present invention and are not intended to limit the scope of the present invention.
[0095] <Example 1>
[0096] Cathode manufacturing
[0097] To prepare the positive electrode, 97.5 wt % of lithium nickel cobalt manganese oxide as a positive electrode active material, 1.0 wt % of carbon black as a conductive material, and 1.5 wt % of polyvinylidene fluoride (PVdF) as a binder were mixed in N-methyl-2-pyrrolidone to prepare a positive electrode slurry.
[0098] An aluminum current collector having a thickness of 15 μm was prepared, and the loading amount of the positive electrode slurry was 600 mg / 25 cm 2The aluminum current collector was coated with the coating material to prepare a positive electrode having a total thickness of 162 μm.
[0099] Anode manufacturing
[0100] To prepare the negative electrode, 80 wt % of silicon (Si) having a D50 particle size of 3 μm as a negative electrode active material, 10 wt % of carbon black as a conductive material, and 10 wt % of a binder were mixed in water to prepare a negative electrode slurry.
[0101] A copper current collector having a thickness of 8 μm was prepared, and the loading amount of the negative electrode slurry was 100 mg / 25 cm 2 The copper current collector was coated with the coating material to prepare a negative electrode having a total thickness of 58 μm.
[0102] Separation membrane manufacturing
[0103] A polyolefin-based separator substrate having a porous structure and a thickness of 9 μm was prepared, and inorganic layers were coated on both sides of the separator substrate using a dip coating method.
[0104] The sum of the thicknesses of the inorganic layers formed on both sides of the separation membrane substrate was 8.5 μm.
[0105] A conductive layer solution was prepared by mixing carbon black and polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP) in a 9:1 weight percent ratio in acetone.
[0106] The conductive layer solution was coated on only one side of each of the inorganic layers formed on both sides of the separator substrate by a slot coating method to a thickness of 2.0 μm, thereby preparing a separator having a conductive layer formed on one side.
[0107] Thus, a separator having a total thickness of 19.5 μm was prepared.
[0108] Battery cell manufacturing
[0109] An electrode assembly was prepared by interposing a separator between the positive electrode and the negative electrode so that the surface on which the conductive layer was formed faced the negative electrode, and an electrolyte was injected to prepare a coin cell.
[0110] <Example 2>
[0111] A battery cell was manufactured using a separator having a conductive layer formed thereon in the same manner as in Example 1, except that the conductive layer formed on one surface of the separator had a thickness of 3.5 μm and the total thickness of the separator was 21.0 μm.
[0112] <Comparative Example 1>
[0113] A polyolefin-based separator substrate having a thickness of 9 μm was prepared, and inorganic layers were coated on both sides of the substrate using a dip coating method.
[0114] The sum of the thicknesses of the inorganic layers formed on both sides of the separator substrate was 8.5 μm, so that the total thickness of the separator was 17.5 μm.
[0115] <Comparative Example 2>
[0116] A polyolefin-based separator substrate having a thickness of 9 μm was prepared, and inorganic layers were coated on both sides of the substrate using a dip coating method.
[0117] The sum of the thicknesses of the inorganic layers formed on both sides of the separator substrate was 10.5 μm, so that the total thickness of the separator was 19.5 μm.
[0118] <Comparative Example 3>
[0119] A polyolefin-based separator substrate having a thickness of 9 μm was prepared, and inorganic layers were coated on both sides of the substrate using a dip coating method.
[0120] The sum of the thicknesses of the inorganic layers formed on both sides of the separator substrate was 12 μm, so that the total thickness of the separator was 21.0 μm.
[0121] <Experimental Example>
[0122] In order to evaluate the life span of each battery cell manufactured in Examples 1 and 2 and Comparative Examples 1 to 3, each battery cell was charged to 4.2 V at 1.0 C and discharged to 3.2 V at 0.5 C for 100 cycles, and the results are shown in Table 1 below.
[0123] [Table 1]
[0124] Referring to Table 1, when a separator including a conductive layer is used, a remaining capacity of 90% or more can be confirmed after 100 charge / discharge cycles.
[0125] Comparing Example 1 and Example 2, when silicon particles having a D50 of 3 μm are used as the negative electrode active material, when a conductive layer is formed to a thickness of 3.5 μm, which is thicker than the D50, as in Example 2, even if cracks occur in the negative electrode active material, the conductive layer complements the conductive network function of the negative electrode active material, thereby maintaining high cycle characteristics.
[0126] Therefore, the thickness of the conductive layer is preferably applied taking into account the D50 of the silicon particles.
[0127] In addition, when comparing Example 1 and Comparative Example 2, and Example 2 and Comparative Example 3, in which the total thickness of the separation membrane is the same, it was found that Comparative Example 2 and Comparative Example 3 had significantly lower cycle characteristics than Example 1 and Example 2, respectively, by forming the inorganic layer thicker.
[0128] Therefore, when a separator having a separator substrate having not only an inorganic layer but also a conductive layer formed thereon is used, it can be seen that the conductive layer has a significant effect on maintaining high cycle characteristics of the battery.
[0129] In addition, when comparing Comparative Examples 1 to 3 in which the thickness of the separation membrane substrate is the same but the thickness of the inorganic layer is different, it can be seen that the thicker the inorganic layer, the greater the resistance to the ionic conductivity of lithium ions, and therefore the worse the cycle characteristics.
[0130] Those skilled in the art will appreciate that various applications and modifications within the scope of the present invention are possible based on the above content. [Industrial Applicability]
[0131] As described above, in the electrode assembly according to the present invention, the conductive layer formed on the surface of the separator can function as a conductive network of the negative electrode mixture layer, so that even if cracks occur in the negative electrode mixture layer due to excessive expansion and contraction of the negative electrode active material, it is possible to prevent interruption of the electron transfer path.
[0132] Furthermore, by limiting the thickness of the conductive layer to a certain range, it is possible to prevent the ion conductivity and output characteristics from being reduced due to the addition of the conductive layer.
[0133] In addition, since a high-capacity silicon active material is used, the negative electrode mixture layer can be formed thinner at the same capacity ratio than when a carbon negative electrode active material is used, and the energy density can be improved by reducing the thickness of the battery cell.
Claims
1. a positive electrode having a positive electrode mixture layer formed on at least one surface of a positive electrode current collector; A negative electrode having a negative electrode mixture layer formed on at least one surface of a negative electrode current collector; and a separator interposed between the positive electrode and the negative electrode; Including, the negative electrode includes the negative electrode current collector and the negative electrode mixture layer, The negative electrode mixture layer contains a silicon active material, A conductive layer is formed on at least one surface of the separation membrane, the thickness of the conductive layer is greater than 50% of the D50 particle size of the silicon active material; The separation membrane is A separation membrane substrate made of a porous substrate; An inorganic layer formed on at least one surface of the separation membrane substrate; and a conductive layer formed on an outer surface of the inorganic layer; Including, A first inorganic layer is formed on one surface of the separation membrane substrate, and a second inorganic layer is formed on the other surface of the separation membrane substrate; an electrode assembly, wherein the conductive layer is formed only on one of the first and second inorganic layers facing the negative electrode;
2. The electrode assembly of claim 1 , wherein the conductive layer comprises a conductive material and a binder.
3. The electrode assembly of claim 1 , wherein the negative electrode active material contained in the negative electrode mixture layer is composed of 100% of the silicon active material.
4. The electrode assembly of claim 1 , wherein the inorganic layer has a structure in which voids are formed.
5. The electrode assembly of claim 1 , wherein the voids formed in the inorganic layer are smaller than the voids formed in the separator substrate.
6. The electrode assembly according to claim 1 , wherein the conductive layer has a porous structure.
7. A battery cell comprising the electrode assembly according to claim 1 housed in a battery case made of a metal can or a laminate sheet.
8. A battery pack including the battery cell according to claim 7 as a unit cell.
Citation Information
Patent Citations
Negative electrode for lithium secondary battery and lithium secondary battery
JP2006196247A
Separator for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2011065984A
Separator for electrochemical device, method of preparation thereof, and electrochemical device comprising the same
KR1020130123568A
KR1999-010035
KR2012-0062713